HUBUNGAN TINGKAT PENGETAHUAN DENGAN KESEDIAAN VAKSINASI COVID-19 PADA WARGA RT 02/05 PERIUK JAYA KOTA TANGERANG TAHUN 2021 - Dyah Safitri (Nusantara Hasana Journal, 2022)
Background: the whole world is experiencing an emergency health problem due to the spread of the corona virus-19 which enters a pandemic condition during a pandemic, as now doing covid-19 vaccination is very much needed by citizens to help increase immunity in the body. A factor that can influence willingness to vaccinate is the level of knowledge about the covid-19 vaccine. Research Objectives: To identify the relationship between knowledge level and readiness for Covid-19 vaccination in residents of RT 02/05 Periuk Jaya. Research Methods: This study uses a descriptive quantitative correlation method with a cross sectional approach. Sampling was carried out using a simple random sampling technique taken at random. Research Results: The data analysis technique used is the Spearman Correlation Test, the results are P-Value 0.042 <0.05. Conclusion: there is a relationship between the level of knowledge and the willingness to vaccinate covid-19 among residents in RT 02/05 Periuk Jaya. Suggestion: it is hoped that citizens will be willing to be vaccinated during the current pandemic.